Refleksi Kritis atas Degradasi Autentisitas Masyarakat Media - Fajar Bayu Aji; Naupal Asnawi Tohir (Jurnal Komunikasi)
The aim of this research is to show that the development of social media in the midst of people's lives cannot be separated from the role of capitalism as an economic global system. Social media, which from the beginning are expected to enable people to access, create, and distribute content without space and time limit. With all the convenience that are presented, social media are   actually faced with spectacle problems. Nowadays through social media, capitalism reads  the desires of the market and offer it’s products that are claimed to lead one to an ideal life, even though it is only fake news. By using the the critical reflection method and knowledge by acquaintance and description method, the researchers analyze the connection between capitalism, social media, and the degradation of authenticity.